Korelasi Identik Sikap Percaya Diri,Kecerdasan Emosional dan Kedisiplinan Belajar terhadap Prestasi Belajar Bahasa Inggris Siswa MAN 1 Wonosobo - Felik Ahmad Mustofa; Maryono Maryono; Faisal Kamal (Jurnal Kajian Ilmu Pendidikan, Bahasa dan Komunikasi, 2025)
This study aims to determine the influence of several psychological factors and learning behavior on the English learning achievement of Madrasah students in Wonosobo Regency. In detail, the objectives of this study include: (1) to determine the influence of self-confidence on the English learning achievement of Madrasah students in Wonosobo; (2) to determine the influence of emotional intelligence on the English learning achievement of Madrasah students in Wonosobo Regency; (3) to determine the influence of learning discipline on the English learning achievement of Madrasah students in Wonosobo Regency; and (4) to determine the influence of self-confidence, emotional intelligence, and learning discipline together on the English learning achievement of Madrasah students in Wonosobo. The type of research used is quantitative with an explanatory research approach. The population of this study was all 161 class X students at MAN 1 Wonosobo. The research sample was determined as many as 164 students using simple random sampling techniques, so that each student has an equal opportunity to become a respondent. Data collection techniques were carried out through documentation and questionnaires. To test the first, second, and third hypotheses, product-moment correlation analysis was used, while for the fourth hypothesis, multiple linear regression analysis was used. The results of the study indicate that: (1) there is a positive and significant influence of self-confidence on English language learning achievement of students at MAN 1 Wonosobo in the 2024/2025 academic year; (2) there is a positive and significant influence of emotional intelligence on learning achievement; (3) there is a positive and significant influence of learning discipline on learning achievement; and (4) there is a simultaneous positive and significant influence between self-confidence, emotional intelligence, and learning discipline on students' English language learning achievement.